Let's first rewrite the given quadratic equation \( y = 6x + 8x + 7 \) in standard form.
Combine the like terms:
\[ y = (6x + 8x) + 7 = 14x + 7 \]
Next, we set the equation equal to zero to find the zeros:
\[ 14x + 7 = 0 \]
Now, let's solve for \( x \):
- Subtract 7 from both sides:
\[ 14x = -7 \]
- Divide both sides by 14:
\[ x = -\frac{7}{14} = -\frac{1}{2} \]
So, the zero of the equation is:
\[ x = -\frac{1}{2} \]
This equation simplified to a linear equation, indicating that it has only one zero, which is \(-\frac{1}{2}\).